Schistosome infection is associated with enhanced whole‐blood IL‐10 secretion in response to cercarial excretory/secretory products. (1st May 2013) - Turner, J. D.; Meurs, L.; Dool, P.; Bourke, C. D.; Mbow, M.; Dièye, T. N.; Mboup, S.; Polman, K.; Mountford, A. P.
Summary Infection of the human host by schistosome parasites follows exposure of skin to free‐swimming cercariae and is aided by the release of excretory/secretory (E/S) material, which is rich in proteases and glycoconjugates. This material provides the initial stimulus to cells of the innate immune system. The study presented here is the first to examine human innate/early immune responsiveness to cercarial E/S in subjects from an area co‐endemic for Schistosoma mansoni and S. haematobium. We report that in infected participants, stimulation of whole‐blood cultures with cercarial E/S material (termed 0–3 hRP) caused the early (within 24 h) release of greater quantities of regulatory IL‐10, compared with uninfected controls. Elevated levels of IL‐10 but not pro‐inflammatory TNFα or IL‐8 were most evident in participants co‐infected with S. mansoni and S. haematobium and were accompanied by a higher 0–3 h RP‐specific IL‐10: TNFα ratio. We also report that glycosylated components within 0–3 h RP appear to be important factors in the stimulation of IL‐8, TNFα and IL‐10 production by whole‐blood cells.